2018
DOI: 10.1002/ijfe.1702
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of global economic policy uncertainty on stock market returns in regime switching environment: Evidence from sectoral perspectives

Abstract: This study contributes in building emerging literature by investigating the impacts of global economic policy uncertainty on Malaysian sectoral stock performance. This study models sectoral stock returns as time‐varying transition probability Markovian processes and employs two‐stage Markov‐switching model for findings impacts of global economic policy uncertainty on sectoral stock returns in regime switching environment. The empirical results reveal that linear framework unable to detect the effects global ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 96 publications
(272 reference statements)
3
37
0
1
Order By: Relevance
“…They found evidence of shock and volatility spillovers between the oil price and stock returns of GCC countries, and the transmission of shock and volatility depends on the economic period and country. More recently, Hoque and Zaidi [51,52] have presented that oil price effects on the Malaysian stock return vary across volatility regime. In support of these empirical studies, this study conjectures that the effects of oil and gas risk factors change over time and vary across volatility state.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…They found evidence of shock and volatility spillovers between the oil price and stock returns of GCC countries, and the transmission of shock and volatility depends on the economic period and country. More recently, Hoque and Zaidi [51,52] have presented that oil price effects on the Malaysian stock return vary across volatility regime. In support of these empirical studies, this study conjectures that the effects of oil and gas risk factors change over time and vary across volatility state.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…While analyzing the impact of economic policy uncertainty on industrial returns, Badshah et al (2018) report positive effect on energy commodities and industrial metals, whereas negative effect on precious metals. Hoque and Zaidi (2018) Prior literature entails different methodologies 1 in examining the effects of EPU on stock returns at firm, industry and market level data. Among GARCH family models, Donadelli and Persha (2014) and Antonakakis et al (2013) utilize DCC-GARCH framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Policy makers can contribute in reducing uncertainty and potential risk in the stock market attributable to high price volatility by decreasing delay in their consensus on frequent change in economic policies.Apart from considering fundamentals and technical aspect of investments, investor should consider the change and impact of economic policies for right prediction of change in stock prices and performance of US stock market. AsHoque and Zaidi (2018) also concluded that EPU impact on sectoral returns should be considered as a part of systematic risk. Industrial level analysis of US equity market returns concludes that EPU contribute positively towards long run volatility of industrial and material industries however negatively towards consumer staples, health care, information technology and materials (also seeYu et al, 2018).…”
mentioning
confidence: 99%
“…The rise of the crude oil price might intensify inflation, cause the growth of the stock discount rate, and induce stock price fluctuation [12]. In contrast, the variation trends of oil price fluctuation and stock market value are generally the same in oil-producing countries [13,14].…”
Section: Literature Reviewmentioning
confidence: 99%